A Sistem Informasi Layanan Kesehatan Berbasis Web Mobile (Studi Kasus Pukesmas BIHA Lampung Barat): Sistem informasi - Susilowati, Tri; Taufik, Taufik; Hartati, Sri (Jurnal Informatika, 2025)
Public Health Centers (Puskesmas) serve as primary healthcare facilities responsible for delivering comprehensive medical services to the community, including promotive, preventive, curative, and rehabilitative efforts. However, in many regions, information management and service administration are still conducted manually. Activities such as patient registration in logbooks, storing physical records, and sharing announcements through limited media remain common practices. These conventional methods often lead to several issues, including delays in providing information, difficulties in retrieving data, potential record loss, and reduced efficiency in health service delivery. Such conditions do not align with the Regulation of the Minister of Health of the Republic of Indonesia No. 31 of 2019, which mandates every Puskesmas to implement an information system to support health service management. Therefore, this study aims to design and develop a Web Mobile-Based Health Service Information System that can be accessed easily anytime and anywhere. The system development process adopts the System Development Life Cycle (SDLC) methodology, which includes six stages: planning, requirement analysis, system design, implementation, testing, and maintenance. The system is developed using PHP, MySQL, HTML, and Bootstrap, resulting in a responsive, userfriendly, and interactive web-based mobile application. The developed system provides several core features, including online patient registration, doctor schedule information, general health services (dental, maternal and child health, laboratory), Puskesmas profile, and a community complaint submission form. Based on testing using the Black Box Testing method, all system functionalities work properly and meet user requirements. The implementation of this system enhances service speed, efficiency, and transparency, while supporting the government’s initiative for healthcare digitalization at the primary service level.